PRA ELIMINATION OF MALARIA SITUATION IN THE DISTRICT OKUS - Maya Arisanti; Rizki Nurmaliani (Jurnal Bahana Kesehatan Masyarakat (Bahana of Journal Public Health), 2019)
Malaria is an infectious disease that is still a global health problem including in Indonesia. To eradicate malaria, the government has launched a malaria elimination movement in all regions of Indonesia with a target of malaria-free Indonesia in 2030. Elimination of malaria in OKUS District is targeted for 2020. The data in this writing come from secondary data from the OKUS District Health Office in 2017 and 2018. Based on these data, the results of the API in OKUS District in 2017 and 2018 are 0.470 / 00 and 0.630 / 00. Plasmodium falciparum is the biggest cause of malaria cases that occurred in OKUS Regency, namely 135 cases in 2017 and 200 cases in 2018. There are still cases of local transmission in OKUS District in the last two years, namely 93 cases in 2017 and 112 cases in 2018 Male malaria sufferers are more compared to female malaria sufferers in 2017, on the contrary in 2018 there are more female malaria sufferers than men. Based on age group, most malaria sufferers occur in the productive age group of 15-64 years, namely 77 cases in 2017 and 112 cases in 2018. Based on the three criteria for malaria elimination, Kabupaten OKUS has fulfilled the API indicator <1 per 1000 inhabitants, but in time brackets in the last two years are still found in cases of local transmission which should not have been a case of local transmission for three consecutive years so that by 2020 it could be proposed for malaria elimination. The active role of the community is needed in malaria eradication activities to prevent malaria transmission from occurring in their area such as eradicating mosquito nests through mutual cooperation activities and increasing understanding of how to prevent mosquito bites through socialization for the community